Analysis Of The Effect Of Current Ratio And Profit Growth On Return On Assets In Cement Sub-Sector Companies Listed On The Indonesia Stock Exchange For The 2012-2021 Period - Nurismalatri, Nurismalatri; Nufzatutsaniah, Nufzatutsaniah; Widianingsih, Tuti (Adpebi Science Series, 2022)
This study aims to determine the effect of the current ratio and profit growth on return on assets in cement sub-sector companies listed on the Indonesia Stock Exchange. The method used in this research is a quantitative method. Data collection techniques used are library research and internet research. The data analysis technique used is panel data regression with a 10 (ten) year time series, namely the period 2012-2021 and 3 (three) cement sub-sector companies. Based on the results of the partial test Current Ratio (X1) has a positive and significant effect on Return On Assets (Y) with a significant value of 0.0000 <0.05. Meanwhile, profit growth (X2) has no effect on return on assets with a significant value of 0.7042 > 0.05.